FAKTORFAKTOR YANG BERPENGARUH TERHADAP PENGELOLAAN ARSIP DINAMIS AKTIF PADA SUBBAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN REMBANG - Muhammad Masruri (STIE Pelita Nusantara Semarang, 2007)
The study uses check list data collecting method which was conducted by filling up the list of question in a way of sign marking in the column given to 54 official employees of Sub Bagian Umum Sekreatariat Daerah Kabupaten Rembang. In analyzing the data, the writer uses a multiple regression. A Relative Contribution (sumbangan Relatif/ SR) being used in testing the hypothesis, to examine the most affecting factor on dynamic and active files management. Along with a statistical software package SPSS 1.2 version.The multiple regression statistic results on Anova testing shows that the value of Fc as 9.45 > F table as 3.476, with the probability lower than 0.05. It means the regression model can be conducted in predicting the dynamic and active files management. In other words, this means that time, tools or means, and finance, at the same time, influencing toward active and dynamic filesmanagement on Sub Bagian Umum Sekretariat Daerah Kabupaten Rembang. The SPSS output shows R square as 0.363, this means that 36.3% of active and dynamic files management variation, can be explained by the three other independent variables included in A Relation Contribution. Ascalculation result in the table, this can be explained that the three independent variables set in the Relative Contribution, show SRX1 as 13.3831% and SRX2 as 63.9511%, and SRX3 as 22.6618%. This means that tools or means have the most dominant influences on active and dynamic files management on Sub Bagian Umum Sekretariat Daerah Kabupaten Rembang, with the acceptanceof SRX2 as 63.9511%.